Fimbristylis sunilii (Cyperaceae): A new species from Southern Western Ghats, Kerala, India - Sanilkumar, Malayil Gopalan; Nithya, Vadassery Madhanan; Divya, Periyattu Veedu; Baiju, Edathiruthi Chandran (Phytotaxa, 2021)
Fimbristylis sunilii, a new species of Cyperaceae, from Western Ghats of Kerala, Southwest India is described and illustrated with photographs. The paper provides distribution and phenology of the new species along with comparison of its allied species.